2016
DOI: 10.1104/pp.15.01487
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Analyses of Angiosperm Nucleotide-Binding Site-Leucine-Rich Repeat Genes Reveal Three Anciently Diverged Classes with Distinct Evolutionary Patterns

Abstract: Nucleotide-binding site-leucine-rich repeat (NBS-LRR) genes make up the largest plant disease resistance gene family (R genes), with hundreds of copies occurring in individual angiosperm genomes. However, the expansion history of NBS-LRR genes during angiosperm evolution is largely unknown. By identifying more than 6,000 NBS-LRR genes in 22 representative angiosperms and reconstructing their phylogenies, we present a potential framework of NBS-LRR gene evolution in the angiosperm. Three anciently diverged NBS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

25
347
3
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 269 publications
(383 citation statements)
references
References 80 publications
(148 reference statements)
25
347
3
8
Order By: Relevance
“…In combination with motif composition analysis of the NBS domain and intron structure and phase detection, our study provides strong evidence that RNL is an ancient NBS-LRR class that has been largely ignored by most previous studies. 6 Thus our results suggest that angiosperm NBS-LRR genes are composed of 3 anciently diverged classes, namely, TNL, CNL, and RNL.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…In combination with motif composition analysis of the NBS domain and intron structure and phase detection, our study provides strong evidence that RNL is an ancient NBS-LRR class that has been largely ignored by most previous studies. 6 Thus our results suggest that angiosperm NBS-LRR genes are composed of 3 anciently diverged classes, namely, TNL, CNL, and RNL.…”
mentioning
confidence: 86%
“…These questions were further addressed in our study by tracing the ancient state of NBS-LRR genes at key divergence nodes of angiosperms step by step. 6 A total of 23 NBS-LRR lineages were finally recovered in the common ancestor of investigated angiosperms. 6 Further comparison of ancestral NBS-LRR lineages at the internal divergence nodes of angiosperm, including mesangiospermae (Ma), eudicots (Ed), monocots (Mo), asterids (As), and rosids (Ro), revealed that 3 NBS-LRR classes underwent distinct evolutionary patterns during angiosperm radiation.…”
mentioning
confidence: 99%
See 3 more Smart Citations